Penegakan Hukum Pidana Lingkungan terhadap Korporasi dalam Perspektif UU PPLH dan Prinsip Strict Liability - Muhammad Karimuallah; Yana Sukma Permana (LPPM Iblam School of Law, 2025)
Environmental criminal law enforcement against corporations remains a crucial issue in Indonesia, particularly in the context of the Environmental Protection and Management Act (UU PPLH) and the application of strict liability. Despite legal recognition of strict liability, its implementation faces various obstacles, including regulatory inconsistencies and corporate legal maneuvers to evade responsibility. This study examines how strict liability is applied in environmental criminal cases and the challenges hindering its effectiveness. A comprehensive understanding of these issues is essential to strengthen environmental law enforcement mechanisms.This research employs a qualitative method with a normative legal approach, focusing on regulatory analysis and legal norm interpretation. Data were obtained through an extensive literature review of primary legal sources, including laws, regulations, and court rulings, supported by secondary sources such as legal journals and academic studies. Findings indicate that although strict liability is theoretically applicable, its enforcement is often inconsistent due to the complexity of corporate structures and limitations in law enforcement capacity. The study also highlights the need for regulatory reinforcement and institutional strengthening to ensure more effective corporate accountability for environmental crimes. Moreover, collaboration between the government, legal practitioners, and civil society is necessary to enhance monitoring and prosecution efforts. Strengthening these aspects can lead to better environmental protection and increased corporate compliance with sustainable business practices.